2019
DOI: 10.1038/s41467-018-07689-7
|View full text |Cite
|
Sign up to set email alerts
|

Compounding tropical and stratospheric forcing of the record low Antarctic sea-ice in 2016

Abstract: After exhibiting an upward trend since 1979, Antarctic sea ice extent (SIE) declined dramatically during austral spring 2016, reaching a record low by December 2016. Here we show that a combination of atmospheric and oceanic phenomena played primary roles for this decline. The anomalous atmospheric circulation was initially driven by record strength tropical convection over the Indian and western Pacific Oceans, which resulted in a wave-3 circulation pattern around Antarctica that acted to reduce SIE in the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
139
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 57 publications
(59 reference statements)
14
139
1
Order By: Relevance
“…Similarly, in our pacemaker experiments we find the observed anticyclonic Rossby wave source off the west coast of Australia ( Figure S6a; dark red patch) to be captured in the Indian ensemble ( Figure S6b), and the cyclonic Rossby wave source off the east coast of Australia ( Figure S6a; dark blue patch) to be due to the combined influences of the Indian ( Figure S6b) and Pacific ( Figure S6c) Oceans. Thus, a Rossby wave source analysis of our pacemaker output complements the observational regression analysis conducted by Wang et al (2019) to disentangle the roles of the Indian and Pacific Oceans in contributing to the high-latitude circulation during September-October 2016 and provides further support for the tropical Indian Ocean driving the zonal wave three pattern at high latitudes.…”
Section: September-october 2016mentioning
confidence: 64%
See 3 more Smart Citations
“…Similarly, in our pacemaker experiments we find the observed anticyclonic Rossby wave source off the west coast of Australia ( Figure S6a; dark red patch) to be captured in the Indian ensemble ( Figure S6b), and the cyclonic Rossby wave source off the east coast of Australia ( Figure S6a; dark blue patch) to be due to the combined influences of the Indian ( Figure S6b) and Pacific ( Figure S6c) Oceans. Thus, a Rossby wave source analysis of our pacemaker output complements the observational regression analysis conducted by Wang et al (2019) to disentangle the roles of the Indian and Pacific Oceans in contributing to the high-latitude circulation during September-October 2016 and provides further support for the tropical Indian Ocean driving the zonal wave three pattern at high latitudes.…”
Section: September-october 2016mentioning
confidence: 64%
“…Anomalies in SST are also overall well reproduced in pattern, if not in magnitude, in this ensemble set. The similarity in MSLP patterns between observations and the Indian ensemble mean, along with a Rossby wave source analysis as in Wang et al (2019; see Figure S6 in the supporting information and discussed below), provides further support that anomalous convection over the eastern Indian Ocean during spring 2016 was a driving force influencing the early phase of the decline in Antarctic sea ice in this season (Meehl et al, 2019;Wang et al, 2019). In response to the anomalous MSLP, the pattern of SIC anomalies also shows a zonal wave three pattern, similar to observed.…”
Section: September-october 2016mentioning
confidence: 96%
See 2 more Smart Citations
“…The decay was particularly strong in November 2016, when Antarctic SIE exhibited a negative anomaly compared to the 1979-2015 average (Schlosser et al, 2018). Several studies have investigated the possible factors driving this recent decline and found it to be linked to a warmer upper Southern Ocean (Meehl et al, 2019), to an anomalous atmospheric circulation with an amplified zonal wave 3 pattern (Schlosser et al, 2018;Wang et al, 2019) and to a significantly weakened polar stratospheric vortex, resulting in record weakening of the circumpolar surface westerlies that acted to decrease SIE (Wang et al, 2019).…”
Section: 1029/2018rg000631mentioning
confidence: 99%